Sources from the history of handicraft production in the Southern Kazakhstan of the second half of XIX – early XX centuries - Alzhanova, E.E. (Publ.KarSU, 2017)
The article discusses the references lighting history of domestic production of the second half of XIX – early XX centuries about domestic production a significant amount of works is written. But most often they are devoted or to separate types of craft, or production of handicraftsmen is considered from ethnographic positions. At the present stage of development of economy of the independent Republic of Kazakhstan domestic production is important, especially in rural zones. However, along with other branches of social production, developments of stagnation of last years, and also a current economic crisis did not pass also this branch of small-scale production. It’s getting out of crisis state, growth of technical equipment of handicraft trade on a modern basis, improvement of system of vocational training of handicraftsmen and handicraftsmen, streamlining of supply of crafts with raw materials, improvement of quality of products of handicraft trade according to requirements of the modern market — all these factors are the most important conditions of growth of efficiency of the modern market relations. In this regard extraction from the past and introduction into the present of wealth of experience of handicraftsmen and handicraftsmen of the Southern Kazakhstan as one of the branches of economy developed economically is represented extremely urgent task of scientists of Kazakhstan of a research of history of handicraft trade. Studying of this branch is urgent not only from the historical point of view, but also as synthesis of data on one of the branches of economy which are important in life of the population of Kazakhstan in general.
XIX ғ. екінші жартысы – XX ғ. басындағы Оңтүстік Қазақстандағы дербес қолөнер өндірісінің тарихы бойынша дереккөздер
Источники по истории кустарно-ремесленного производства Южного Казахстана второй половины XIX – начала XX вв.
Keywords: handicraft production; colonialist nature; colony; the development of the productive forces sources